Management of Chronic Myeloid Leukemia and Pregnancy: A Bibliometric Analysis (2000-2020) - Wang, Yue; Jiang, Liqing; Li, Baoxuan; Zhao, Yan (Frontiers in Oncology, 2022)
Background: Given the increasing number and survival rates of reproductive-age patients with chronic myeloid leukemia (CML), several studies aimed to elucidate optimum disease management in pregnancy. This study aimed to use bibliometric analysis to assess focus and reported insights, as well as future trends, in CML and pregnancy research. Methods: We extracted all studies related to CML and pregnancy from the Web of Science database from 2001 to 2020. VOS Viewer, CiteSpace, Python, and R-bibliometrix were used for bibliometric analysis, revealing the leading research countries, institutions, and authors, as well as distribution of keywords (frequency greater than five). Results: A total of 196 records, published in 137 journals by 1,107 authors from 422 research institutes in 43 countries, were identified for analysis. The United States was the leader in the number of publications. Imperial College London, and Heidelberg University were the most influential institutions. In addition, Abruzzese, Kantarjian, and Ault were the leading authors in the field. Keyword analysis identified four research hotspot clusters. Conclusions: This study systematically analyzed the progress in CML and pregnancy research in the last 20 years. The present findings suggest that the management of planned and unplanned pregnancies in patients with CML will remain a research focus, as further evidence is required for the development of treatment guidelines.